Quercetin and catechin assuage redox imbalance and neurochemical dysfunction in rotenone-induced neurotoxicity: A comparative in vivo experiment supported by in silico study - Sunday Solomon Josiah; Haruna Isiyaku Umar; Ibrahim Olabayode Saliu; Afolabi Clement Akinmoladun (Elsevier, 2021)
Background: Quercetin and catechin are structurally-related compounds that are capable of preventing or attenuating oxidative damage and mitochondrial dysfunction. Rotenone is a naturally occurring compound that has been used to model neurotoxicity characterized by Parkinson disease-like symptoms. Purpose: This study investigated the comparative property of quercetin and catechin, to ameliorate oxidative damage and neurochemical dysfunction in hippocampal and cortical regions of brain of rats intoxicated with rotenone in vivo, supported by in silico study. Method: Male Wistar rats were subcutaneously administered rotenone for 10 days followed by post-treatment with catechin or quercetin (5, 10 and 20 mg/kg) for 3 days. Markers of oxidative stress and neurochemical dysfunction were biochemically estimated in the hippocampus and cortex of the brain of rats while in silico study was carried out to evaluate the molecular interaction of some neurochemical enzymes with the compounds. Result: Quercetin and catechin ameliorated the reduction in complex 1 and Na+K+ATPase activities while attenuating the elevated lactate dehydrogenase activity in the brain of rotenone-intoxicated rats. Disturbances in acetylcholine, dopamine and glutamate metabolism as well as the evoked oxidative stress in rotenone-intoxicated rats were mitigated by quercetin and catechin. The in silico study revealed the key molecular interaction between the flavonoids and targeted enzymes (tyrosine hydroxylase, monoamine oxidase, glutamine synthetase and Na+K+ATPase) to be by hydrogen bond and hydrophobic interaction. Conclusion: Catechin and quercetin significantly assuaged cortical and hippocampal redox stress and attenuated neurochemical dysfunction caused by rotenone toxicity. Furthermore, this study highlighted that the neuroprotective potentials of the flavonoids is a function of their structural patterns, and quercetin elicited superior activity over catechin due to its structural advantages.